Dinamika Kompetensi Profesional Guru dalam Meningkatkan Capaian Hasil Belajar Santri dalam Pembelajaran Kitab Jurumiyah - Zidna Sabilarrizqi; Milna Wafirah (MUADDIB: Jurnal Pendidikan Agama Islam, 2026)
Students’ learning outcomes serve as a critical indicator of the success of the educational process within Islamic boarding schools (pesantren). In the context of learning the Jurumiyah book, the teacher’s professional competence is a pivotal factor, as it determines the clarity, systematic delivery, and comprehensibility of nahwu (Arabic grammar) material. This study aims to analyze the influence of teachers’ professional competence on students’ learning outcomes in the Jurumiyah course at the API Asri Islamic Boarding School in Tegalrejo, Magelang. Employing a quantitative approach with an associative research design, this study involved 168 students from the Marḥalah Śāliśah level, selected through stratified random sampling. Data were collected via questionnaires and documentation, then analyzed using SPSS version 26, incorporating validity, reliability, normality, homogeneity, simple linear regression, t-tests, and coefficient of determination tests. The results demonstrate that teachers’ professional competence has a positive and significant influence on students’ learning outcomes. This is statistically confirmed by a significance value of 0.000 (< 0.05), leading to the rejection of H0 and the acceptance of Ha. Furthermore, the coefficient of determination (R2) of 0.687 indicates that teachers’ professional competence contributes 68.7% to students’ learning outcomes, while the remaining 31.3% is attributed to external factors not examined in this study. This research underscores the vital role of pedagogical professionalism in enhancing the quality of classical text instruction within the pesantren ecosystem.